Development of Novel Catalytic Direct Syntheses of N-Unsubstituted Ketimines and Their Applications to One-Pot Reactions - Kondo, Yuta; Morimoto, Hiroyuki; Ohshima, Takashi (Synlett, 2023)
Herein, we summarize our recent efforts toward developing catalytic methods for the synthesis of N-unsubstituted ketimines and their applications to one-pot reactions for producing various nitrogen-containing compounds. This account provides detailed background, optimization, scope, and mechanistic information. We hope this work will stimulate future studies on the implementation of N-unsubstituted ketimines.1 Introduction2 Scandium-Catalyzed Synthesis of N-Unsubstituted Ketimines3 Tetra-n-butylammonium Fluoride Catalyzed Synthesis of N-Unsubstituted Ketimines4 Conclusion
Keywords: N-unsubstituted ketimines; one-pot reactions; amino acid derivatives; scandium triflate; tetrabutylammonium fluoride